Ammonium oxalate-extractable uronic acids positively affect biomass enzymatic digestibility by reducing lignocellulose crystallinity in Miscanthus. (November 2015) - Wang, Yanting; Huang, Jiangfeng; Li, Ying; Xiong, Ke; Wang, Youmei; Li, Fengcheng; Liu, Mingyong; Wu, Zhiliang; Tu, Yuanyuan; Peng, Liangcai
Highlights: Uronic acids-rich wall polymers positively affect biomass saccharification. Uronic acids of AO-extracted components play a major role in biomass digestion. Uronic acids negatively affect lignocellulose CrI for high biomass digestibility. Potential modification of uronic acids-rich polymers in bioenergy Miscanthus . Abstract: Based on systems biology analyses of total 179 representative Miscanthus accessions, ammonium oxalate (AO)-extractable uronic acids could either positively affect biomass digestibility or negatively alter lignocellulose crystallinity at p < 0.01 or 0.05. Comparative analysis of four typical pairs of Miscanthus samples indicated that the AO-extractable uronic acids, other than hexoses and pentoses, play a predominant role in biomass enzymatic saccharification upon various chemical pretreatments, consistent with observations of strong cell tissue destruction in situ and rough biomass residue surface in vitro in the unique Msa24 sample rich in uronic acids. Notably, AO-extraction of uronic acids could significantly increase lignocellulose CrI at p < 0.05, indicating that uronic acids-rich polymers may have the interactions with β-1, 4-glucan chains that reduce cellulose crystallinity. It has also suggested that increasing of uronic acids should be a useful approach for enhancing biomass enzymatic digestibility in Miscanthus and beyond.